2022
DOI: 10.1111/bcpt.13765
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the DNA repair enzymes MTH1 and OGG1 as a novel approach to treat inflammatory diseases

Abstract: Autoimmune diseases and acute inflammation like sepsis cause significant morbidity and disability globally, and new targeted therapies are urgently needed. DNA repair and reactive oxygen species (ROS) pathways have long been investigated as targets for cancer treatment, but their role in immunological research has been limited. In this MiniReview, we discuss the DNA repair enzymes MTH1 and OGG1 as targets to treat both T cell-driven diseases and acute inflammation. The MiniReview is based on a PhD thesis where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The IC50 value obtained was 20.4µM, which clearly manifests the effectiveness of RV in suppressing the enzymatic activity of MTH1 at the micromolar range (Figure 6A). Given the reported overexpression of MTH1 in various cancers [10][11][12][13][14][15][16][17][22][23][24][25][26][27][28][29][30][31][32][33], the inhibitory potential of RV on cancer cell progression was studied. The MCF7 cell line was used for all the cell-based biological assays due to the well-established expression of MTH1 in breast cancer [18][19][20]55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IC50 value obtained was 20.4µM, which clearly manifests the effectiveness of RV in suppressing the enzymatic activity of MTH1 at the micromolar range (Figure 6A). Given the reported overexpression of MTH1 in various cancers [10][11][12][13][14][15][16][17][22][23][24][25][26][27][28][29][30][31][32][33], the inhibitory potential of RV on cancer cell progression was studied. The MCF7 cell line was used for all the cell-based biological assays due to the well-established expression of MTH1 in breast cancer [18][19][20]55].…”
Section: Discussionmentioning
confidence: 99%
“…Those mentioned above in silico study, followed by the fluorescence binding study and inhibition study, clearly established the efficient binding and significant inhibition of MTH1 by compound RV. Given the reported overexpression of MTH1 in various cancers [10][11][12][13][14][15][16][17][22][23][24][25][26][27][28][29][30][31][32][33], the inhibitory potential of RV on cancer cell progression was studied. All the cell-based studies were conducted on the MCF 7 cell line, as the overexpression of MTH1 is widely reported in breast cancer [18][19][20]55].…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Important efforts from different groups have led to the identification and characterization of inhibitors against BER proteins such as PARP1, APE1 and OGG1 (Li et al, 2021). Very promising observations were made with the OGG1 competitive inhibitors TH5487 and SU0268 that have been proposed to be potential new tools for cancer therapy (Visnes et al, 2020) and for the treatment of inflammatory diseases (Visnes et al, 2018b;Karsten, 2022). Beside the promising potential use of OGG1 inhibitors for therapeutical purposes, these molecules represent also valuable tools in fundamental research and have brought important information concerning OGG1 molecular mechanisms, in both repair and transcriptional regulation (Hanna et al, 2020;Hao et al, 2020;Qin et al, 2020;Xia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…2 Dr. Stella Karsten from Sweden was awarded the BCPT Young Investigator's Award 2022 for her Mini Review "Targeting the DNA repair enzymes MTH1 and OGG1 as a novel approach to treat inflammatory diseases" based on her PhD thesis defended in 2021. 3 The troubled financial markets all over the world have also influenced BCPT, but fortunately, we have a very solid economy. For as long as it is possible, the Association for the Publication of BCPT will support scientific meetings in the Nordic countries.…”
mentioning
confidence: 99%
“…Stage, University of Southern Denmark, was awarded the BCPT Young Researcher Award 2022 in Basic and Clinical Pharmacology 2 . Dr. Stella Karsten from Sweden was awarded the BCPT Young Investigator's Award 2022 for her Mini Review “Targeting the DNA repair enzymes MTH1 and OGG1 as a novel approach to treat inflammatory diseases” based on her PhD thesis defended in 2021 3 …”
mentioning
confidence: 99%